PENGARUH FUNGSI INTERMEDIASI TERHADAP DANA PIHAK KETIGA DAN KREDIT PADA BANK UMUM DI KOTABANDA ACEH - Elidar Elidar; Ratna Mutia (Politeknik Negeri Lhokseumawe, 2016)
This study, entitled Analysis of General Bank Intermediation Function in Banda Aceh. This study aimed to analyze the function of intermediation of commercial banks in the city of Banda Aceh. Bank is one of the institutions the operational confidence to collect funds and channel them back to the community, in this case means that people believe save their money in banks and banks are also believed to lend to the public. Bank has a function as an intermediary who was instrumental in pushing the national economy as well as areas that can be measured from the Loan to Deposit Ratio (LDR) which shows the ratio of a bank or a comparison between the magnitude of the ability of banks to provide loans to the public with the whole amount of funds that can be raised from the public. The data used is secondary data monthly time series of the year 2010-2015 and analyzed using multiple regression. Based on the results of research analyzes the influence of third-party funds (DPK), interest rates (SB) and Non Performing Loan (NPL) in general bank acquired 77.69 percent of the dependent variable intermediation (LDR) can be explained by the independent variable and the remaining 22.31 percent LDR variation is explained by other variables. Simultaneously variable DPK, SB and NPL significant effect (real) against a common bank intermediation function in the city of Banda Aceh. Partially if a variable size third party funds (DPK) generated in this analysis is significant, it can be assumed that the third party funds affect the intermediation role of general banks in the city of Banda Aceh, while changes in SB conventional banks affect the intermediation of general banks in the city Banda Aceh. The higher the percentage of NPL ratio indicates the worse the quality of credit and finance portfolio. In the end, a reduction in the performance of the intermediary function of the bank because the bank will be more stringent in finance and credit portfolio given the bank must perform the recovery of funds of funds that do not come back from the financing and credit defaults.Keywords: Loan Deposit Ratio (LDR), Third Party Funds, Interest Rates, and Non Performing Loan (NPL).